High data rate transmissions in UWB system using orthogonal pulses - LIANG Zhao-hui1; DU Hong-feng1; ZHOU Zheng1 (Tongxin xuebao)
Two orthogonal pulses based on wavelet were presented,their spectrum meet FCC spectral mask for ultra wideband （UWB） system.A novel method for high data rate transmissions in UWB system was proposed.It employs a combination of pulse polarity and orthogonal pulses shape modulation and implements high date rate by transmitting more bits simultaneously.